Has the ‘best interests of the child' principle been applied to children's rights in Botswana on maintenance, custody and adoption matters? - Mokibe, Linah (Department of Public Law, 2025)
Botswana has a pluralistic legal system. Thus customary law operates parallel to the Constitution, the common law as well as statute laws. Children in Botswana are subject to all these laws and systems. At international level, Botswana has acceded to the United Nations Convention on the Rights of the Child and has ratified several other international and regional human rights instruments. The UNCRC is an international treaty which lays down the social, economic, political, civil, health and cultural rights of all children. It is the basic human rights treaty which recognizes that children are also equal as human beings. Despite Botswana's accession to the UNCRC, which provides that the ‘best interests of the child' shall be the paramount consideration in all decisions made regarding a child, there is still a lack in the application of this principle when decisions relating to children are made on maintenance, custody and adoption. This study therefore interrogates whether there is an indication that the best interests of the child principle has been applied on children's rights in Botswana when decisions are made on maintenance, custody and adoption of children.